2009
DOI: 10.1074/jbc.m109.040832
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Pulmonary Surfactant Phospholipids Inhibit Inflammatory Responses from Alveolar Macrophages and U937 Cells by Binding the Lipopolysaccharide-interacting Proteins CD14 and MD-2

Abstract: Lipopolysaccharide (LPS), derived from Gram-negative bacteria, is a major cause of acute lung injury and respiratory distress syndrome. Pulmonary surfactant is secreted as a complex mixture of lipids and proteins onto the alveolar surface of the lung. Surfactant phospholipids are essential in reducing surface tension at the air-liquid interface and preventing alveolar collapse at the end of the respiratory cycle. In the present study, we determined that palmitoyl-oleoyl-phosphatidylglycerol and phosphatidylino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
203
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(221 citation statements)
references
References 56 publications
(43 reference statements)
14
203
3
Order By: Relevance
“…Previous studies have provided evidence that the antagonism of LPS activation through LBP/CD14/MD2/TLR4 is dependent upon the molecular class and species of phospholipid used as an antagonist (17)(18)(19)(20). We examined the molecular specificity of the POPG effect on RSV-elicited cytokine production by comparing the effects of POPG with a phospholipid counterpart containing a choline polar moiety, palmitoyl-oleoylphosphatidylcholine (POPC).…”
Section: Popg Specifically Attenuates Proinflammatory Cytokine Producmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have provided evidence that the antagonism of LPS activation through LBP/CD14/MD2/TLR4 is dependent upon the molecular class and species of phospholipid used as an antagonist (17)(18)(19)(20). We examined the molecular specificity of the POPG effect on RSV-elicited cytokine production by comparing the effects of POPG with a phospholipid counterpart containing a choline polar moiety, palmitoyl-oleoylphosphatidylcholine (POPC).…”
Section: Popg Specifically Attenuates Proinflammatory Cytokine Producmentioning
confidence: 99%
“…In human pulmonary surfactant, POPG is the most abundant molecular species present within the PG class of phospholipid. Recent findings now indicate that selected surfactant lipids and proteins may complement each other in the homeostatic suppression of inflammation in the lung (17,21,22).We have undertaken a comprehensive examination of the role of POPG in regulating multiple aspects of innate immunity. As part of this endeavor we focused upon the interrelationships between CD14, POPG, and RSV.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 Now, his team has shown that POPG directly binds RSV in vitro and reduces viral infection and lung pathology in vivo. 1 In RSV-infected epithelial cell lines, POPG liposomes prevented both viral spread to neighboring cells and cell death.…”
mentioning
confidence: 99%